Development of a Gold Nanoparticle-Based ELISA for Detection of PCV2 - Basso, Caroline Rodrigues [UNESP] (2024)
In this new methodology, plasmonic ELISA (pELISA) was used to detect Circovirus porcine2 (PCV2) in serum samples without the need for plate reading equipment. This process occurs by adapting the conventional ELISA test with gold nanoparticles (AuNPs) to promote a color change on the plate and quickly identify this difference with the naked eye, generating a dark purple-gray hue when the samples are positive and red when the samples are negative. The technique demonstrated high efficiency in detecting samples with a viral load ≥ 5 log10 copies/mL. Plasmonic ELISA offers user-friendly, cost-effective, and reliable characteristics, making it a valuable tool for PCV2 diagnosis and potentially adaptable for other pathogen detection applications.